The Effect of Self Assessment and Tax Knowledge on Tax Compliance - Asih Machfuzhoh; Intan Puspanita (PT. EQUATOR SINAR AKADEMIA, 2021)
Tax is the main income of the State. Unfortunately, citizens who fulfill their tax obligations are not balanced with the total population in Indonesia. This is a problem, how to increase tax compliance, to increase the tax ratio, so that income from taxes can be maximized. Many studies examine the factors that affect tax compliance. This research will examine the effect of self-assessment and tax knowledge on tax compliance of taxpayers. The sample of this study was 80 respondents, with the criteria of a private person in the city of Serang, who had a TIN and worked. The results of this study indicate that self assessment and tax knowledge have a positive and significant impact on tax compliance, either partially or simultaneously.